Analisis Yuridis Perbuatan Penipuan dengan Modus Giveaway dalam Perspektif Undang-Undang ITE - Nyoman Candradevi Triantini; I Nyoman Sujana; I Made Aditya Mantara Putra (Verdict: Journal of Law Science, 2026)
This study evaluates deceptive practices involving the giveaway scheme through the lens of the ITE Law. The investigation primarily centers its attention upon regulations that have not explicitly mentioned fraudulent acts using the giveaway method in legislation, thus giving rise to conflicting norms between laws. This study focuses on analyzing: how is the legal regulation of fraudulent acts using the giveaway method in Indonesia and how is the law enforced against perpetrators of fraud using the giveaway method. This inquiry employs a normative legal research design, integrating legislative, theoretical, and judicial precedent perspectives. The results indicate that although Indonesian legislation does not explicitly regulate giveaway fraud as a distinct criminal offense, such conduct can nevertheless be prosecuted under the existing legal framework. The fraudulent giveaway schemes currently fall under the jurisdiction of Article 492 of the Criminal Code (lex generalis) and Article 28 subsection (1) of the ITE Law (lex specialis). Perpetrators of fraud will be punished in accordance with the applicable legal basis in order to pay attention to the application of the principle of lex specialis derogat legi generali as a basis for determining norms to realize legal certainty and provide protection to victims of technology-based fraud. The findings provide guidance for law enforcement agencies, including investigators, prosecutors, and judges, in determining the appropriate legal basis for prosecuting giveaway fraud conducted through electronic media. The recognition of electronic information and electronic documents as valid evidence further strengthens the effectiveness of criminal investigations and prosecutions in cybercrime cases.